MODEL OF ARRANGING FISHERMEN'S SETTLEMENT AREAS BASED ON STILT HOUSES AND FLOATING HOUSES AS AN ADAPTIVE SOLUTION TO CLIMATE CHANGE AND STRENGTHENING REGIONAL RESILIENCE IN MUARA ANGKE, NORTH JAKARTA - Yanda Dwira Firman Z (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The fishermen's settlement area in Muara Angke, North Jakarta, faces serious challenges due to tidal flooding, poor infrastructure, and a clean water crisis. The Republic of Indonesia Defense University (Unhan RI) initiated a pilot project for area arrangement using stilt houses and floating houses as adaptive solutions. This article examines a multidisciplinary approach involving physical development, clean water and sanitation systems, as well as strengthening the community's social capacity. The methodology includes field observation, community participation, and technical infrastructure analysis. The results show that the application of modular technology, desalination systems, and waste treatment can improve quality of life and environmental resilience. This model has the potential to be replicated in other coastal areas in Indonesia, strengthening community resilience and territorial defense through a community-based civil defense approach, while also supporting geostrategic strategies and national policies for coastal area management.